Comparative Study of IoT Platforms and Support for Edge Computing - Bhawna Nigam, Dr.; Dugar, Himanshu; Singh Bhatia, Tanveer (International Journal of Engineering and Technology, 2018)
The Internet of Things has power to make oneâ€™s life comfortable and overcome challenges that people face even in their daily life. Today facilities like smart healthcare, smart homes, smart grid, remote monitoring of devices have become an indispensable part of our lives, the reason being Internet of things. To create smart devices, applications are rapidly moving to the cloud, because amount of data generated is increasing tremendously. But there are some applications that require real time processing, low latency, support for mobility, very large number of nodes, working in remote areas. These applications demand edge computing where data is stored and processed near the end device. IoT connects physical devices and facilitates them to communicate with each other and control them remotely. Now we are entering an era where the applications require data to be stored and processed at the periphery of the network. In this paper our focus is on study of Iot applications, core IoT services providing platforms based on cloud computing, their comparison, challenges and support for edge computing. Â Â